2021
DOI: 10.1371/journal.pone.0256027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a care bundle for patients with blunt chest injury (ChIP): A multicentre controlled implementation evaluation

Abstract: Background Blunt chest injury leads to significant morbidity and mortality. The aim of this study was to evaluate the effect of a multidisciplinary chest injury care bundle (ChIP) on patient and health service outcomes. ChIP provides guidance in three key pillars of care for blunt chest injury—respiratory support, analgesia and complication prevention. ChIP was implemented using a multi-faceted implementation plan developed using the Behaviour Change Wheel. Methods This controlled pre-and post-test study (tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Theory can be used to identify the clinical behaviour being targeted for change and find techniques to modify it 22 . In our hospital, as we have previously described, this consisted of monitoring of compliance, performance feedback, role modelling, training, education and enablement 26 . Next steps could include multi‐disciplinary monthly trauma case reviews, not restricted only to trauma committee members, but all those who are involved in managing trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Theory can be used to identify the clinical behaviour being targeted for change and find techniques to modify it 22 . In our hospital, as we have previously described, this consisted of monitoring of compliance, performance feedback, role modelling, training, education and enablement 26 . Next steps could include multi‐disciplinary monthly trauma case reviews, not restricted only to trauma committee members, but all those who are involved in managing trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…(Curtis et al, 2017). The context suitability should also need to be considered, using a tool such as the APEASE criteria (APEASE criteria: Affordability, Practicality, Effectiveness and cost-effectiveness, Acceptability, Side-effects/safety and Equity) (Michie et al, 2011), which has been shown to be an important tool for evaluating a concept for intervention (Curtis, Kourouche, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Intervention functions are ‘broad categories by means of which an intervention can change behaviour’ [ 20 ]. We used this approach successfully to test interventions in the ED previously (2021) [ 10 , 24 , 25 ]. The implementation toolkit will be refined for each cluster using mechanisms from the behaviour change techniques taxonomy and the APEASE criteria that consider affordability, practicality, effectiveness/cost-effectiveness, acceptability, side-effects/safety, and equity [ 20 ].…”
Section: Methodsmentioning
confidence: 99%